Premorbid disorders of pancreatic functional state in children with chronic gastroduodenal pathology - T.V. Sorokman; V.G. Ostapchuk (Zaslavsky O.Yu., 2018)
Background. Secondary pancreatic insufficiency in pediatric practice happens increasingly frequently and can occur at any age, both against the background of nutritional deficiencies, and various inflammatory diseases of the upper parts of the digestive tract. The purpose was to investigate the pancreatic functional state in children with chronic gastroduodenal pathology. Materials and methods. The study was conducted on the basis of the gastroenterology unit of the Chernivtsi Regional Clinical Children's Hospital during 2013-2018. The basic clinical group consisted of 64 children aged 8-18 years with chronic gastroduodenal pathology: 29 patients had chronic gastritis, 30 persons had chronic gastroduodenitis, 5 people had peptic ulcer. All children underwent general clinical studies, ultrasound of the abdominal organs, fibrogastroduodenoscopy, pH-metry, 3-fold coprologic examination; there were determined the activity of a-amylase, serum lipase, urine diastase, feces elastase (FE-1) concentration in feces, serum C-peptide, blood glucose level, and an oral glucose-tolerant test was performed. Statistical processing of the obtained data was carried out by means of the programs Statistics 6.0. Results. The key manifestations were pain (93.7 %), dyspepsia (90.6 %), astheno-neurotic syndromes (57.8 %), a violation of the motor-evacuation function of the stomach and duodenum as a gastroesophageal and duodenogastric reflux. 35.9 ± 3.7 % of the patients developed the signs of pancreatic lesion: thickening of the tail of the pancreas and ultrasonic hyperechoic, amylorrhea, creatorrhoea, type I and II steatorrhoea, changes in the a-amylase level, FE-1, 'flat' curves of glucose tolerance test, that indicated the initial disturbances of carbohydrate metabolism. Median C-peptide for children of the basic group was 1.29 ng/ml (CI 1.11-3.42), for children of the comparison group 0.89 ng/ml (CI 0.23-1.12). The tendency to C-peptide level increasing was registered in 12 over-weighted children. These children have a 'flat' glucose test curve, as well as a violation of the exocrine function of pancreas manifested with ultrasonic changes. Conclusions. The revealed changes in the pancreatic functional state in the examined children indicate the need to determine the functional state of the gland and its control in the dynamics of treatment of gastroduodenal pathology.